A new species of Phrynobatrachus (Anura: Phrynobatrachidae) from the Eastern Arc Mountians of Tanzania - Pickersgill, Martin; Zimkus, Breda M.; Raw, Lynn R. G. (Zootaxa, 2017)
Phrynobatrachus discogularis sp. nov. (Anura, Phrynobatrachidae) is described from the Eastern Arc Mountains in Tanzania. It occupies upland grasslands and while it morphologically most resembles West and Central African P. gutturosus (Chabanaud, 1921), P. rungwensis (Loveridge, 1932), and P. anotis Schmidt and Inger, 1959, preliminary analysis of mitochondrial 16S rRNA indicates that the new species differs from all other species with published sequence data by a minimum distance of 4.1% and has affinities with P. rungwensis, P. uzungwensis Grandison and Howell, 1983 and P. keniensis Barbour and Loveridge, 1928—all diminutive upland eastern African taxa. The shape and colour of the male’s external gular apparatus distinguish this species from all other described Phrynobatrachus species. Although geographically either sympatric or closely allopatric with P. uzungwensis, the lack of overlapping morphological characters indicates the two forms are distinct species. The new taxon is compared with other species from the region.